Praktek Hutang Piutang Badan Usaha Milik Desa Di Merbau Mataram Kabupaten Tanggamus Perspektif Hukum Islam - Nafisah, Jauharotun; Munawaroh, Nurlaila Fitri; Karini, Eti (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research is about the practice of accounts payable in Merbau Mataram BUMDes, Tanggamus Regency, for capital or micro business loans. The focus of the problem in this study is how is the practice and what is the view of Islamic law regarding borrowing or debt receivables of the BUMDes Fund in Merbau Village, West Kelumbayan District, Tanggamus Regency? The purpose of this study was to find out the practice and find out the views of Islamic law on lending BUMDes funds in Merbau Village, West Kelumbayan District, Tanggamus Regency. This research method uses a qualitative method with the type of field research (field research) conducted on the Practice of Borrowing BUMDes Funds in Merbau Village, Kelumbayan Barat District, Tanggamus Regency, using a descriptive qualitative method. Using primary and secondary data sources, by looking at the population and sample. Collection techniques were carried out through observation, observation, documentation and interviews with village officials and loan recipient customers. Based on the results of the research, it is known that the practice of lending funds in BUMDes Merbau Mandiri BUMDes lends funds to people who want to do small and medium businesses with repayments in installments according to the agreement at the time of the contract. The margin or interest rate is not determined by the BUMDes manager but is determined based on the ability of the borrower, then the practice of lending funds that occur in the BUMDes of Merbau village, Kelumbayan Barat District, Tanggamus Regency in terms of consent and acceptance in accordance with the pillars and conditions of al-qardh, namely sighah, aqidain, assets owed and there is no provision for what percentage of services must be provided to BUMDes.Keywords: Al-Qardh, BUMDes, Sharia Economic Law